Awareness of comfort immediately after a relaxation therapy session affects future quality of life and autonomic function: a prospective cohort study on the expectations of therapy - Hasuo, Hideaki (Biopsychosoc Med, 2018)
BACKGROUND: High expectations regarding therapy are reported to have positive effects on future therapeutic course and related behavior. Some individuals are aware of feelings of comfort immediately after a relaxation therapy session. METHODS: Heart rate variability biofeedback (HRV-BF) therapy using a relaxation technique called resonant breathing was administered to 44 family caregivers who felt burdened by their work caring for family members with cancer. We prospectively evaluated how the level of comfort participants were aware of immediately after an initial therapy session affected their expectations regarding the therapy, as well as future quality of life (QOL) and autonomic function. This study was a secondary analysis of a randomized, open-label study titled “Self-care system for family caregivers of cancer patients using resonant breathing with a portable home device”. RESULTS: Among the participants, 56.8% were aware of a feeling of comfort immediately after an initial therapy session. Participants were then divided into two groups according to the presence or absence of their awareness of comfort. Expectation levels regarding the therapy were significantly increased in the awareness group after the therapy session (P = 0.003). No main effect between groups was observed for heart rate variability (HRV) during therapy (P = 0.949). Four weeks after the initial therapy session, QOL improved and HRV increased in the awareness group (P < 0.001). CONCLUSIONS: Better outcomes in the awareness group were not associated with HRV during therapy. A feeling of comfort immediately after a therapy session may have positive effects on future QOL and autonomic function by raising participants’ expectations of the therapy. TRIAL REGISTRATION: UMIN000021639. Registered 27 March 2016